LIMFOSIT T CD4+SEBAGAI PERAMAL PERJALANAN PENYAKIT PASIEN YANG MENGALAMI SEPSIS - Lestari Ekowati; Aryati Aryati; Hardiono Hardiono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Sepsis is the most common cause of ICU mortality in USA. Mortality of sepsis in developing countries is still very high, about 50- 70% and has became a 80% incidence in septic shock. There was a decrease of CD4+ T lymphocyte count in patients with sepsis caused by apoptosis indicating septic patients suffered from immune functional impairment. CD4+ T lymphocyte count can reflect the severity of sepsis and predict the prognosis of the patients with sepsis effectively. Eighty eight (88) patients who met sepsis criteria were studied. The researchers collected clinical variables of all patients within 24 hours diagnosis of sepsis, and calculated APACHE II score. At the same time, blood sample were taken to measure the CD4+ T lymphocyte count. The data were analyzed using independent Student-T-test and ROC curve was used for prognosis. There is a significant difference in CD4+ T lymphocyte count between non survival and survival group (non survival group 203±178 cells/μL, survival group 442±303 cells/μL, p<0.001), and the percentage of CD4+ T lymphocyte (non survival group 25.05±11.55%, survival group 34.38±9.15%, p<0.001). There is an under ROC curve for CD4+ T lymphocyte count was 0.81, and for the percentage of CD4+ T lymphocyte was 0.748. Cut off value for CD4+ T lymphocyte count was 204 cells/μL, and the percentage of CD4+ T lymphocytes was 25.23%. Based on this study, the CD4+ T lymphocyte count can be used as a predictor of prognosis in sepsis patients.